Digital nomads: who are they? - Fikry, Amily; Sani, Azurin; Syed Omar, Syed Ashrene; Mohamed Thaheer, Ahmad Shazeer; Suib, Fatin Husna (Human Resource Management Academic Research Society (HRMARS), 2023)
The world has experienced many changes in the era post-COVID-19. Remote work arrangements have recently emerged as a working model in which professionals work outside the traditional office environment. The number of remote workers is expected to increase in the years to come in the post-pandemic era. With the growing trend of remote work arrangements, more people experienced leisure travel without detachment from work. Hence, this paper aims to provide a holistic definition of a digital nomad. In doing so, past articles from 2009 until 2023 have been reviewed, analysed, and the definition provided from past articles have been extracted and compiled. The paper concludes with a holistic definition of digital nomads and its implications for practitioners.